Ultrasound examination of the normal fetal duodenum - Xiao, Huibin; Li, Hongbo; Chen, Xiaozhu; Lin, Xiaoyan; Liang, Xiaoqin; Jiang, Huoyong; Wang, Hongchan; Lu, Wenyue; Li, Fengrong; He, Zhenping (Frontiers in Surgery, 2023)
Objective To use the fetal pylorus as a reference point to conveniently display the normal fetal duodenum by ultrasound. Methods This study was designed in cross-section. A total of 450 healthy singleton pregnant women at 19-39 weeks of gestation who underwent prenatal screening at our hospital from January 2019 to February 2020 were selected. They were divided into three groups according to gestational weeks: the 19–23 gestational weeks group, 29–32 gestational weeks group, and 34–39 gestational weeks group. The duodenal bulb was identified. Its movement and course were continuously and dynamically observed. The descending part of the duodenum was identified, and the duodenal course was traced. Results The fluid-filled in the fetal duodenum was discontinuous. The overall detection rates of the duodenum in the 19–23 gestational weeks group, 29–32 gestational weeks group, and the 34–39 gestational weeks group were 82.2%, 26.2%, and 13.8%, respectively. The detection rates of the bulbar, descending, horizontal, and ascending parts of the duodenum were 94.4%, 58.2%, 58.0%, and 52.0%, respectively. The anatomical structures of the duodenum as a whole and the pancreas were most easily recognized in the 19–23 gestational weeks group; while in the 34–39 gestational weeks group, the bulbar part had a maximum detection rate of 98.8%, and it had the longest filling time and the shortest examination time. Conclusion The pylorus is an ideal starting point for tracing the fetal duodenum. The overall detection rate of the fetal duodenum decreases with gestational age. The duodenal bulb is the most easily detected site.